Mobile climbing robot with energy recovery - M. Polishchuk; V. Oliinyk (Mechanics and Advanced Technologies)
This paper presents a novel method of improving energy efficiency of climbing robot by implementing accumulation of motion energy and its further recycling. Patented construction and functional scheme of pedipulator – conceptual walking mechanism are provided as well as a method to integrate movement and surface attachment modules of the robot. Calculations of dynamic loads are provided followed by results of simulations that demonstrate effective approach implementation by changing kinematic or constructional parameters instead of dynamic